Powiązanie krajowych cen pszenicy z cenami europejskimi i światowymi - Figiel, Szczepan (Connection of Domestic Wheat Prices with European and World Prices, 2005)
An increasing openness of Polish economy to trade linkages with other countries should be reflected in the price development observed on the domestic agricultural markets. The purpose of this paper is to determine to what extent adjustments preceding accession to the EU, which have occurred in Polish agribusiness sector in the last several years, had an impact on connection of domestic wheat prices with selected European and world prices. Results of an econometric analysis carried out for the period of 1990-2004 show that most of the price adjustment process took place in the beginning of the 1990s and in the mid of the 1990s Polish wheat prices became fairly well connected with the USA and French wheat export prices. In the last years of the analyzed period short term relationship between the examined prices weakened slightly, however, they continued to converge along with coming a long term relationship into existence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 197-202